HASIL PENELITIAN YURIDIS PELAKSANAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KOTA CILEGON - Adinda Permata Putri; Endang Suparsetyani (Fakultas Hukum Universitas Trisakti, 2022)
Complete Systematic Land Registration (PTSL), a process to concurrently register land for the first time for all land objects to be registered in Indonesia. The issue is how the PTSL is being implemented in Cilegon City in accordance with the relevant laws. What challenges and initiatives does the Cilegon City Land Office encounter in its PTSL Program Activities? Research is the normative legal technique, qualitatively assessed, and deductive reasoning. According to Ministerial Regulation No. 6 of 2018 governing PTSL, this paper's conclusion is that PTSL in Cilegon City has gone through 13 stages. The challenges faced are a lack of public information regarding costs, completeness of proof of land ownership and complementary processes from previous applicants, overlapping, broken land histories, incompatibility of juridical data with physical data on land parcels, slow signing process by the village committee team, designation of field boundaries not attended by the applicant and boundary neighbors. As well as the efforts made are counseling related to PTSL insights, counseling to complete evidence of land ownership, improving the quality of juridical data and physical data, subject data collection for counseling invitation letters, coordinating with the Cilegon city government, involving the government and Cilegon city officials.